Evaluation of the Efficacy of Triclabendazole in Naturally Infected Sheep with Fasciola species at Bonga Sheep Breeding and Improvement Center, South West Ethiopia - Warkaw Merachew; Tewodros Alemneh; Motuma Debela (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Fascioliasis is the most important parasitic disease that affects humans and animals all over the world. Triclabendazole (TCBZ) is the most common drug used for the treatment of fasciolosis. This study was conducted in Bonga Sheep Breeding and Improvement Center, Kefa Zone, Ethiopia to evaluate the efficacy of Triclabendazole against Fasciola species (Fasciola hepatica and Fasciola gigantica) in naturally infected sheep. An experimental study design and purposive sampling procedure were employed from the source of sheep population. The study included 20 Bonga sheep breed naturally infected with Fasciola species and purposively selected based on their clinical signs, symptoms and faecal egg counts. Twenty (20) sheep of 2-4 years old, irrespective of sex, infested with Fasciola species were selected for this experiment and randomly divided into two equal groups (treatment and control group, n=10) each consisted of 10 sheep. Faecal samples were collected from each sheep before and after treatment. McMaster method was used to count faecal eggs. The efficacy of Triclabendazole was determined by Faecal Egg Count Reduction Test (FECRT). Descriptive statistics (means, standard error of mean and reduction percentages) were calculated to manage data. The percentage reduction in mean faecal egg count, after 14 and 21 days of treatment for Triclabendazole were 96.51% and 97.18%, respectively. Generally, this finding indicated that Triclabendazole was found effective against Fasciola species in the study area. However, appropriate use of this anthelmintic is credible to prevent future occurrence of resistance.